Improvement of moral competence in university students: An intervention through moral emotions - Robles Francia, Víctor Hugo; De la Cruz - Caballero, Adriana Mariela; Banda Guzmán, Judith; Robles-Ramos , Víctor Adrián (Acta Universitaria, 2022)
This paper analyzes the effectiveness of an intervention to improve moral competence in university students. The intervention was carried out through deliberation on emotional dilemmas, perception, and communication of moral emotions by participants. The research design was quasi-experimental, adopting a pretest-posttest design. The control and experimental groups were made up of 26 students. The moral competence of all participants was evaluated using the emotional moral competence index (EMCI). The participants in both groups were chosen based on a very low level of moral competence, an average value (EMCI = 20) below population mean (EMCI Mean = 31.8; EMCISD = 11.8). The effectiveness of the intervention was assessed using the difference between the means and the univariate linear regression analysis of the two groups. The results of the experimental group showed significant values and important effects in the increase of moral competence after the intervention.